Quality Assessment of Tomato Paste Products on the Ghanaian Market: An Insight Into Their Possible Adulteration - Abena Boakye; Doreen D. Avor; Isaac K. Amponsah; William O. Appaw; Leslie Owusu-Ansah; Silas Adjei; Michael K. Baah; John N. Addotey (International Journal of Food Science)
Tomato paste is the most consumed tomato product on the Ghanaian market, the majority of which are imported into the country. This food product is easily adulterated, and thus, routine quality checks are necessary. Therefore, the current study is aimed at assessing the quality of eight tomato paste products on the Ghanaian market and checking for the presence of starch and artificial colourant erythrosine as possible adulterants. Routine quality metrics such as the pH, titratable acidity, total solids, and total soluble solids were assessed using standard methods. An HPLC method was employed to detect the presence of the colourant erythrosine, whereas starch content was determined by an enzymatic method using α-amylase and then amyloglucosidase. Fifty percent of the products did not qualify to be called tomato paste based on total solid estimation. All the sampled products contained some amount of starch, with three having more than 10 g/100 g of this thickener. Additionally, the banned colourant erythrosine was detected in two of the products. All other parameters were consistent with regulatory standards. The present study has shown that some tomato paste products on the Ghanaian market contain additives that are not permitted under any circumstance and fall short of regulatory standards.